2011
DOI: 10.1051/0004-6361/201116834
|View full text |Cite
|
Sign up to set email alerts
|

Filaments and the magnetic configuration. I. Observation of the solar case

Abstract: Context. The emission of Ca and Hα is correlated for the Sun, but this does not seem to be true for other stars. We previously demonstrated that this lack of correlation could be due to the presence of filaments. Aims. We aim to establish a link between the activity level, the magnetic configuration, and the number of filaments, and therefore with observables of other stars that the Sun. Methods. We studied the relationship between the filaments and the magnetic configuration using a large scale approach on MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Rust 1966;Kuperus & Tandberg-Hanssen 1967;Hirayama 1985;Mouradian 1998;Ulrich et al 2002). Meunier & Delfosse (2011) quantified this relationship based on a systematic comparison of filament positions and magnetograms. However, there are more PIL pixels during cycle minimum, and less during cycle maximum because of the presence of large unipolar areas, while there are far fewer filaments during cycle minimum.…”
Section: Filament Propertiesmentioning
confidence: 99%
“…Rust 1966;Kuperus & Tandberg-Hanssen 1967;Hirayama 1985;Mouradian 1998;Ulrich et al 2002). Meunier & Delfosse (2011) quantified this relationship based on a systematic comparison of filament positions and magnetograms. However, there are more PIL pixels during cycle minimum, and less during cycle maximum because of the presence of large unipolar areas, while there are far fewer filaments during cycle minimum.…”
Section: Filament Propertiesmentioning
confidence: 99%
“…Meunier et al 2010a,b, Lagrange et al 2010, Borgniet et al 2015, Marchwinski et al 2015. Meunier & Delfosse (2011) found that the correlation between the Hα and the CaII activity indices depends on the activity cycle.…”
Section: The Sun As a Starmentioning
confidence: 99%